The influence of the postulates of the French Revolution in the Constitution of 1823 - Pazo Pineda, Oscar Andrés (2021)
Peruvian constitutionalism of the 19th century has several inspiring sources. There is no doubt that one of the main ones was the Spanish, which was due to the historical and cultural ties that united us to that nation. However, we shouldn’t lose sight of the importance that other movements had in the subsequent evolution of our constitutions. In this sense, the case of the French Revolution should be highlighted, which was a movement with universal tendencies whose postulates left an important mark on Peruvian thinkers of that time. This research highlights the main areas in which it has been possible to notice the French influence in the first Peruvian constitutional text. For this purpose, it is specified what the French Revolution meant and how it impacts in our country. Subsequently, the important role that, in this influence, the Declaration of the Rights of Man and of the Citizen of 1789 in the first Peruvian constitutionalism of the 19th century, and, especially, in the text of 1823, is highlighted.